SEMANTIC ANALYSIS OF APHORISMS IN THE ENGLISH AND UZBEK LANGUAGES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article presents a comparative semantic analysis of aphorisms in the English and Uzbek languages. Aphorisms are concise, expressive statements that convey generalized wisdom and cultural experience through implicit and metaphorical meanings. The study aims to identify the main semantic features of aphorisms, analyze their meaning structure, and reveal similarities and differences in semantic representation across the two languages. The research applies descriptive, semantic, and contrastive methods. The findings show that while English aphorisms tend to emphasize pragmatism, rationality, and individual experience, Uzbek aphorisms are more oriented toward moral values, spirituality, and collective consciousness.